“INFLUENCE OF MOTIVES, KNOWLEDGE AND SKILLS ON EMPLOYEE PERFORMANCE AT PT INACON LUHUR PERTIWI ENGINEERING CONSULTANTS AND MANAGEMENT JAKARTA” - Rachmawati, Mariana; Imanudin; Zaelani, Senita Apriliani; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to obtain the results of the study and analysis of the influence of knowledge, skills and motives on employee performance at PT Inacon Luhur Pertiwi Engineering Consultants and Management Jakarta. These characteristics are complex competencies. Different knowledge that each employee needs skills that match their work and expertise, such as employee expertise in Engineering, and employees have expertise in marketing management in increasing employee productivity in solving company problems, and employees having good skills in carrying out work, such as, employees Having skills Concern for Order, Initiative, Information Seeking, employees must have high motivation, in several factors of intrinsic motivation, namely, Responsibility, Reward, Work itself, Development and progress, so that good employee performance can be achieved. The results of this study are in improving employee performance, the main thing is to increase motivation, as well as improve skills and knowledge. The conclusions from the results of the research on employee performance at PT Inacon Luhur Pertiwi Engineering Consultants and Management Jakarta are influenced by motives, knowledge and skills. high level of knowledge and skills.